Effective policy communication: Targets versus instruments - Francesco D'Acunto; Daniel Hoang; Maritta Paloviita; Michael Weber (Bank of Finland, 2020)
Communication targeting households and firms has become a stand-alone policy tool of many central banks. But which forms of communication, if any, can reach ordinary people and manage their economic expectations effectively? In a large-scale randomized control trial, we show that communication manages expectations when it focuses on policy targets and objectives rather than on the instruments designed to reach such objectives. It is especially the least sophisticated demographic groups, whom central banks typically struggle to reach, who react more to target-based communication. When exposed to target-based communication, these groups are also more likely to believe that policies will benefit households and the economy. Target-based communication enhances policy effectiveness and contributes to strengthen the public's trust in central banks, which is crucial to ensure the effectiveness of their policies.
URN:NBN:fi:bof-202011022476
Keywords: D12; D84; D91; E21; E31; E32; E52; E65; 330; Behavioral Macroeconomics; Heterogeneous Beliefs; Limited Cognition; Expectations Formation; Household Finance